Effect of the ethanolic extract of Randia aculeata’s fruit in heart and skeletal muscle oxidative stress caused by snake venom - Gallardo Casas, Carlos Ángel; Castillo Hernández, María del Carmen; Ayala Hernández, Marcos; Sánchez Maldonado, Hugo Alberto Alberto; Cano Europa, Edgar (Medicina e Investigación Universidad Autónoma del Estado de México, 2022)
The purpose of this investigation was to prove if Randia aculeata is able to protect against oxidative stress generated by snake’s venom. Forty-eight male CD1 mice were used divided in groups of 8. 1) control group, 2) Randia aculeata, 3) Bothrops asper venom, 4) Randia aculeata and Bothrops asper, 5) Crotalus simus venom and 6) Randia aculeata and Crotalus simus. Blood was obtained and then fibrinogen, Lactate Dehydrogenase ( ldh ) and Creatin kinase ( ck ) were quantified. Muscle and hearts from animals were obtained in order to analyse Lipid-peroxidation ( lpx ), and antioxidant enzymes (catalase, super oxide dismutase [ sod ], and glutathione peroxidase, [ gpx ]). Mice treated with the venom had an increase in ck and ldh enzyme activity. Fibrinogen decreased. These disturbances were prevented with the administration of extract. It also prevented increasing levels of lipoperoxidation in both organs. It was found that sod , catalase and gpx enzyme activity in skeletal muscle, were not altered. In heart tissue, sod and gpx decreased levels were found in groups that received the venom, but ethanol extract prevented this decrease. Catalase activity increased in groups treated with snake venom, and the one that received venom from C. simus and ethanol extract. The plant minimizes significantly.